OCB EVALUATION AND MOTIVATION IN IMPROVING PRIVATE LECTURER PERFORMANCE IN SURAKARTA CITY FROM REWARD ASPECT - Praptiestrini, Praptiestrini; Haryono, Haryono (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The phenomenon that occurs in private universities in Surakarta city today, is related to efforts to improve the quality of accreditation of study programs in each faculty. Some of the things behind these problems include the increasing demands for accountability of higher education institutions, the community's need to know how much quality has been achieved by higher education institutions. In addition, the influence of globalization requires the mechanism of private universities to create competitive advantages that are oriented towards quality assurance. This study aims to analyze the effect of rewards on lecturer performance through OCB and motivation at six universities in the city of Surakarta. The population is lecturers who work in six private universities in the city of Surakarta. The number of samples of 100 respondents was calculated by the Slovin formula. The analysis technique using Path Analysis. The results showed (1) reward has a significant effect on OCB and motivation (2) motivation has a significant effect on lecturer performance while reward and OCB are not significant (3) reward has no significant effect on performance (4) motivation is effective as an intermediary reward variable in influencing lecturer performance.